Towards an Integrated Understanding of Demographic Change and its Spatio-Temporal Dimensions: Concepts, Data Needs and Case Studies - Klüsener, Sebastian; Szoltysek, Mikolaj; Goldstein, Joshua R. (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
Demographic change is a macro-phenomenon, driven by decisions and events at the individual level. However, individual-level events are often influenced by the spatial socioeconomic context in which the actors are embedded. This context usually changes slowly over time which suggests that the present circumstances depend to a large extent on past developments. In this paper, we outline how a GIS-based empirical research approach can deepen our understanding of the spatio-temporal dimensions of demographic change. This approach can benefit from the concepts and methods of at least three disciplines: demography, geography and historical sciences. In addition, we describe the recent improvements in the (geo-)data infrastructure, with the goal of overcoming data limitations that have so far restricted research in this field. Three case studies illustrate the potential of such an approach.